Instructional materials in advanced reading - Dulay, Braulio M. 1927- (s.n.], 1974)
This study contains instructional materials for advanced reading. The materials address the needs of advanced learners, specifically third and fourth year high school students. Four instructional materials, each divided into two main parts, were used. The first part is an essay and the second part involves exercises drawn from the essay.